A Facile Synthesis of Pechmann Dyes. Issue 19 (2nd April 2014) - Hopf, Henning; Jones, Peter G.; Nicolescu, Alina; Bicu, Elena; Birsa, Lucian M.; Belei, Dalila
Abstract A facile synthesis of Pechmann dyes has been accomplished by the reaction of substituted N‐phenacyl‐4‐dimethylaminopyridinium halides with dimethyl maleate in the presence of DBU. Based on a related 4‐DMAP elimination product and an isolated monolactone intermediate a reaction mechanism has been proposed. The scope of this synthetic method is determined by the availability of α‐haloaroyl or heteroaroyl derivatives. DBU=1, 8‐diazabicycloundec‐7‐ene, DMAP=4‐dimethylaminopyridine.